Договірні засади реалізації регіональної політики України. - Іжа, М.М.; Ижа, М.М.; Izha, М. (My University, 2011)
The legal foundation of contractual relations between the govern- ment and regions are considered. The main advantages and disadvantages of the Agreement on regional development between the Cabinet of Ministers of Ukraine and regional councils are analyzed.
Іжа М.М. Договірні засади реалізації регіональної політики України. / М.М. Іжа // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 12-18 . С.124 - 137.
Keywords: Договірні відносини; Регіональний розвиток; Державне управління регіонами; Государственное управление регионами; Региональное развитие; Договорные отношения; contractual relationship; Regional development; Public administration regions